An Imperative of a Poorly Recognized Existential Risk: Early Socialization of Smart Young Generation in Information Society - Fomichov, V. A.; Fomichova, O. S. (Informatica, 2014)
An Imperative of a Poorly Recognized Existential Risk: Early Socialization of Smart Young Generation in Information Society